The benchmarking procedure: Implementation in the case of proton backscattering - Paneta, V.; Colaux, J.; Gurbich, A.; Jeynes, C.; Kokkoris, M.; Lagoyannis, A. (HNPS Advances in Nuclear Physics, 2019)
The benchmarking procedure in IBA regards the validation of charged-particle differential cross- section data via the acquisition of EBS spectra from uniform thick target of known composition followed by their detailed simulation. In the present work such benchmarking measurements have been performed for the elastic scattering of protons on 23Na, 31P and natS in the energy range of 1– 3.5 MeV in steps of 250 keV at three backward angles, at 120.6°, 148.8° and 173.5° in order to validate the corresponding existing evaluated cross-section datasets from SigmaCalc and to facilitate their extension at higher energies. The measurements were performed using the 2 MV Tandetron Accelerator of the Ion Beam Center of the University of Surrey. The EBS spectra acquired were compared with simulated ones using the DataFurnace code, along with an a posteriori treatment of the surface roughness. All the experimental parameters were thoroughly investigated and the results obtained and the discrepancies found are discussed and analyzed. Moreover, the benchmarking procedure in complicated cases, such as the natB(p,p) studied at NCSR “Demokritos”, where background contributions exist, is also discussed.